Public participation in the Geoweb era: Defining a typology for geo-participation in local governments. (February 2019) - Zhang, Shanqi
Abstract: Advancements in citizen sensing and geospatial big data have enabled new opportunities for government-citizen interactions and have played important roles in developing smart(er) cities. In addition to city governments and citizens actively using maps to communicate spatial planning issues, the increasing capabilities of citizens generating spatial data either actively or passively allow city governments to collect local spatial knowledge with unprecedented breadth at finer spatiotemporal resolutions. New methods for citizens collaborating with city governments are also emerging to enhance citizen engagement and to spur social innovation. By synthesizing recent advancements in geo-enabled citizen participation, this paper proposed a new typology for classifying and characterizing concepts and practices related to geospatial technology-mediated public participation in local governments (e.g. city and municipal governments). Practical examples are used to illustrate how new dynamics between local governments and citizens are formed, new methods of collecting local spatial knowledge are enabled, and new opportunities for improving the openness and operational efficiency of local governments have emerged. The proposed conceptualization and examples give rise to emerging needs of advancing geo-participation by developing geospatial methods and infrastructure and by investigating the social and spatial implications of geo-participation.